Implementation and Transfer of Predictive Analytics for Smart Maintenance: A Case Study - von Enzberg, Sebastian; Naskos, Athanasios; Metaxa, Ifigeneia; Köchling, Daniel; Kühn, Arno (Frontiers in Computer Science, 2020)
Smart maintenance offers promising potentials to increase efficiency of the maintenance process, leading to a reduction of machine downtime and thus an overall productivity increase in industrial manufacturing. By applying fault detection and prediction algorithms to machine and sensor data, maintenance measures (i.e. planning of human resources, materials and spare parts) can be better planned and thus machine stoppage can be prevented. While many examples of Predictive Maintenance (PdM) have been proven successful and commercial solutions are offered by machine and part manufacturers, wide-spread implementation of Smart Maintenance solutions and processes in industrial production is still not observed. In this work, we present a case study motivated by a typical maintenance activity in an industrial plant. The paper focuses on the crucial aspects of each phase of the PdM implementation process, towards the holistic integration of the solution within a company. A concept is derived for the model transfer to a different factory. This is illustrated by practical examples from a lighthouse factory within the BOOST 4.0 project. The quantitative impact of the deployed solutions is described. Based on empirical results, best practises are derived in the domain and data understanding, the implementation, integration and model transfer phases.